2002
DOI: 10.1046/j.1440-1789.2002.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia lesions in ‘Pick complex’: A topographic neuropathological study of 19 autopsy cases

Abstract: The distribution of basal ganglia lesions, including the amygdala, striatum (caudate nucleus, putamen), pallidum, and substantia nigra, were reinvestigated in 19 Japanese autopsy cases of 'Pick complex', consisting of five patients with corticobasal degeneration (CBD), 10 patients with Pick's disease with Pick bodies (PDPB), and four patients with generalized variant of Pick's disease (gvPD). The lesions in the amygdala, striatum, and pallidum were classified into three categories (severe, moderate, and slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although previous neuroimaging 7, 912, 17, 18, 40, 41 and histopathological studies 2123 have noted general striatal involvement in FTD, this study provides a systematic investigation of striatal subregion atrophy in early bvFTD, SD, and AD. By focusing on specific striatal subregions and using manual volumetric methods better suited to delineate and quantify these structures, we identified pan-striatal atrophy in bvFTD and more selective putamen and NAcc atrophy in SD.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although previous neuroimaging 7, 912, 17, 18, 40, 41 and histopathological studies 2123 have noted general striatal involvement in FTD, this study provides a systematic investigation of striatal subregion atrophy in early bvFTD, SD, and AD. By focusing on specific striatal subregions and using manual volumetric methods better suited to delineate and quantify these structures, we identified pan-striatal atrophy in bvFTD and more selective putamen and NAcc atrophy in SD.…”
Section: Discussionmentioning
confidence: 84%
“…Abundant striatal tau pathology, manifesting as NCIs, DNs, GCIs, and white matter threads, has been widely reported in patients with FTLD-tau 23 . In this study, we found severe NAcc atrophy in SD, which rarely results from FTLD-tau 31, 45, 46 , and we explored this finding in available neuropathological materials.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting phenotype includes motor symptoms such as tremor, bradykinesia, muscle rigidity and postural instability that resemble parkinsonism, which were amendable to pharmacological intervention (Ittner et al, 2008;Van Eersel et al, 2010). Such extrapyramidal symptoms are common in FTLD, along with striatal atrophy and neuronal loss, fibrillary gliosis and reduced dopamine transporter binding in caudate/putamen (Rinne et al, 2002;Tsuchiya and Ikeda, 2002;Josephs et al, 2008;Looi et al, 2009;Whitwell et al, 2009;Halabi et al, 2013). These striatalbased changes correlate with the degree of extrapyramidal motor symptoms, as well as with compulsive and repetitive behavioural symptoms in bvFTLD (Rinne et al, 2002;Josephs et al, 2008;Halabi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%